Strategies, approaches, and best practices of inclusive education in regular schools: Systematic literature review - I. Isyatirradhiyah; A. Afandi; Reni Marlina; Lynda Kurnia Agustina (Universitas Muhammadiyah Malang, 2025)
Inclusive education is a strategic approach that aims to ensure that all learners, including those with special needs, receive equal and quality education services in regular schools. Although it has become an important part of the education system in many countries, the implementation of inclusive education faces various challenges, such as limited resources, lack of teacher competence and less than optimal collaborative support from all stakeholders. This study conducted a systematic review of strategies, approaches and best practices that have been implemented to optimize the implementation of inclusive education in regular schools. The results emphasize the need to strengthen ongoing teacher training, increase collaboration among stakeholders and implement adaptive and innovative learning strategies. The implications of these results suggest the importance of developing policies that support continuous training and enforcing closer collaboration at the school and community levels. Strategic recommendations include increasing teachers' capacity through continuous training, using inclusive learning strategies and varied media, and a comprehensive evaluation system. The findings are expected to serve as a reference for educators, policy makers and school managers in designing and implementing effective and sustainable inclusive education policies.